Hepatocellular adenoma: imaging review of the various molecular subtypes. Issue 4 (April 2017) - Dharmana, H.; Saravana-Bawan, S.; Girgis, S.; Low, G.
Abstract : This educational review focuses on the epidemiology and radiological evaluation of the various subtypes of hepatic adenomas (HCAs). It includes detailed discussion of the imaging appearances of each HCA subtype and the clinical relevance of the new classification system. Each HCA subtype has a unique biological behaviour. Imaging plays a central role in diagnosis, subtype characterisation, identification of complications, and follow-up assessment. Management of patients should vary according to the specific HCA subtype.